Investigation of a Lodged Bullet inside a Human Brain using Computed Tomographic (CT) Imaging - Getasew Admasu Wubetu (Ethiopian Journal of Science and Sustainable Development, 2023)
We reported the location of a lodged bullet inside a human brain from the 2D and 3D images using Computed Tomography (CT). It is based on the scanning of the hard and the soft tissues of the brain as well as a bullet by X-ray photons on the circular 3600 CCD detectors. The absorption on the target brain and the bullet had significant differences in the measured current (mA) and the mapped Hounsfield Unit (HU) as a function of the number of slices. The 2D and the reconstructed 3D images displayed the brain soft tissue, which was dark with low HU compared to the white in the bullet part with a higher HU.  The attenuation coefficients of a bullet with Copper (Cu) and the skull of the brain with Calcium (Ca) were higher than that of the brain soft tissues with Hydrogen (H) and Oxygen (O). A typical example is the observation of the image at the center of the slices displayed brighter at 3071 HU. 3D structures of brain images were generated and visualized in different viewing positions. The measured value for a lodged bullet was 11.28 cm away from its entry (Frontal), 7.92 cm from the back, and 6.96 cm deep, down from the upper part of the brain. Based on our analysis, the bullet is located in the left hemisphere, which is part of the hypothalamus and parity.